Ameliorating Effect of Malva neglecta Wallr on Obesity and Diabetes in Wistar Rats: A Mechanistic Study. (28th May 2022) - Akhtar, Muhammad Furqan; Farooq, Umar; Saleem, Ammara; Saleem, Mohammad; Rahman, Md Habibur; Ashraf, Ghulam Md
Abstract : A high caloric food causes deposition of fats that may progress to obesity. Obesity is a risk factor for various metabolic and cardiovascular diseases, including but limited to diabetes mellitus. This study is aimed at determining the ameliorating effect of Malva Neglecta wallr aqueous-methanolic extract (MNME) on obesity and diabetes in Wistar rats. The MNME was chemically characterized by high-performance liquid chromatography (HPLC). The plant extract was evaluated by in vitro α -amylase inhibition and DPPH scavenging activities. Obesity was induced by administering high sugar and fat diet (HSFD) to rats for six weeks, followed by intraperitoneal injection of alloxan monohydrate (150 mg/kg) to induce diabetes. Oral treatments with MNME 250, 500, and 750 mg/kg/day were given to diabetic obese rats for 14 days. The HPLC analysis showed the presence of phenolic acids and flavonoids. The plant extract showed significant antioxidant (P < 0.001 ) and alpha-amylase (P < 0.0001 ) inhibition activities. The administration of MNME displayed a considerable decrease in fasting blood glucose, body weight, liver function tests, urea, cholesterol, leptin, and insulin levels in diabetic obese rats as compared to the disease control group and maximum effect were observed at 750 mg/kg/day of MNME. The MNME significantly increased (P < 0.05 − 0.001 ) the levels of GSH, SOD, and CAT in the liver, kidney, and pancreas while notably (P < 0.05 − 0.001 ) reduced the malondialdehyde level in kidney and pancreas of diabetic obese rats in contrast to disease control rats. This experimental study concludes that the MNME had exhibited antiobesity and antidiabetic activities through reduction of oxidative stress, leptin, α -amylase activity, and insulin resistance due to the presence of phenolic acid and flavonoid compounds.